2012
DOI: 10.1111/j.1557-9263.2012.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Stable-hydrogen isotope turnover in red blood cells of two migratory thrushes: application to studies of connectivity and carry-over effects

Abstract: valores de discriminación calculados para los glóbulos rojos colectados en el sitio reproductivo de ambas especies fueron mayores de lo esperado en base a estudios que utilizan la queratina. La renovación durante la migración actualmente limita la utilidad de usar muestras de sangre colectadas tempranamente en la temporada de reproducción para estudios de conectividad/arrastre. Sin embargo, la tecnología de seguimiento directo como geolocalizadores puede proporcionar información sobre la duración de la migraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Cellular blood turnover in Wood Thrushes likely takes at least 2 weeks (McKinnon et al. ). The trend we observed of a decline in δ 15 N in the forest habitats may reflect the beginning of an underlying shift in diet that, because of the time‐lag between consumption and tissue turnover, would not be apparent in blood values until later in April.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular blood turnover in Wood Thrushes likely takes at least 2 weeks (McKinnon et al. ). The trend we observed of a decline in δ 15 N in the forest habitats may reflect the beginning of an underlying shift in diet that, because of the time‐lag between consumption and tissue turnover, would not be apparent in blood values until later in April.…”
Section: Discussionmentioning
confidence: 99%
“…For example, isotope values of the cellular blood of songbirds represent diet over a period of 2–3 weeks (McKinnon et al. ), and thus are not biased toward recently consumed foods. Stable isotope analysis also provides an advantage because fruits may be difficult to detect in emetic or fecal samples, especially if seeds are not consumed.…”
mentioning
confidence: 99%
“…The most parsimonious explanation for this pattern and why it differs from that observed for winter-collected tissues discussed above is that muscle and blood have not equilibrated with local hydrogen sources when these birds were collected in Tierra del Fuego in early February. d 2 H isotopic incorporation rates have not been quantified for liver, muscle, or whole blood, but McKinnon et al (2012) found that d 2 H half-life estimates for red blood cells in two species of migratory thrushes varied from 14 to 21 days. Wolf et al (2012) and Storm-Suke et al (2012) reported similar incorporation rates for d 2 H of red blood cells in captive Japanese quail; half life estimates for plasma in quail were ;3.5 days.…”
Section: Importance Of Isotopic Incorporation: Oustaleti and Patagonimentioning
confidence: 99%
“…[54]) could also result in important spatio-temporal variation in δ 2 H f of ASY songbirds from a given region, but it is unclear to what extent resources consumed during the nesting period can be integrated in tissues that have grown during the post-fledging period (e.g. [55, 56]).…”
Section: Discussionmentioning
confidence: 99%